2015
DOI: 10.7717/peerj.1276
|View full text |Cite
|
Sign up to set email alerts
|

Successful survival, growth, and reproductive potential of quagga mussels in low calcium lake water: is there uncertainty of establishment risk?

Abstract: The risk of quagga mussel (Dreissena rostriformis bugensis Andrusov 1897) establishment into water-bodies of the western US has expanded the geographic concern regarding the ecological and economic impacts this species will have in aquatic ecosystems. Thresholds based on calcium concentrations, an element critical for mussel growth and physiology, have been used as a primary predictor of quagga mussel establishment success to aid management decisions. We evaluated the invasion potential of quagga mussels in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Bivalve mollusks require calcium for the formation of their shells, and several studies have indicated that [Ca 2+ ] is often an important environmental predictor of the presence of freshwater bivalves (Davis et al, 2015;Lucy et al, 2012;McMahon, 1996). However, the minimum [Ca 2+ ] required for dreissenid growth and survival is poorly constrained and may vary between species and even between life stages within a species (Davis et al, 2015).…”
Section: Implications For Invasive Bivalvesmentioning
confidence: 99%
See 3 more Smart Citations
“…Bivalve mollusks require calcium for the formation of their shells, and several studies have indicated that [Ca 2+ ] is often an important environmental predictor of the presence of freshwater bivalves (Davis et al, 2015;Lucy et al, 2012;McMahon, 1996). However, the minimum [Ca 2+ ] required for dreissenid growth and survival is poorly constrained and may vary between species and even between life stages within a species (Davis et al, 2015).…”
Section: Implications For Invasive Bivalvesmentioning
confidence: 99%
“…However, the minimum [Ca 2+ ] required for dreissenid growth and survival is poorly constrained and may vary between species and even between life stages within a species (Davis et al, 2015). Applying the reported [Ca 2+ ] needed for growth and survival of dreissenid mussels, Neary and Leach (1992) ] (e.g., <12 mg L À1 ) is likely to limit the establishment and thus the spread of invasive bivalves (Davis et al, 2015;Oliveira, Calheiros, Jacobi, & Hamilton, 2011;Strayer et al, 1996). Therefore, the results we report in this short communication indicate that there is usually sufficient [Ca 2+ ] in the lower CR to support the establishment of invasive dreissenid mussels, which could join the currently widespread and abundant Asian clam (C. fluminea) as the newest bivalves to invade an already heavily invaded CR ecosystem.…”
Section: Implications For Invasive Bivalvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on laboratory studies, Davis et al. (2015) suggested that water bodies with 12–15 mg/L of calcium were at risk of invasion by quagga mussels. Whittier et al.…”
Section: Introductionmentioning
confidence: 99%